Presidential Decree-Laws Nos. 15 and 24 of the Year 2014 Amending Some Provisions of the Law on the Regulation of Universities As Promulgated by Law No. 49 of the year 1972 - egypt (2025)
Presidential Decree-Law No. 15 of the year 2014 amending some provisions of the law on the regulation of universities, as promulgated by law no. 49 of the year 1972 -- Presidential Decree-Law No. 24 of the year 2014 amending certain provisions of the law on the regulation of universities, as promulgated by law no. 49 of the year 1972 قرار رئيس جمهورية مصر العربية بالقانون رقم 15 لسنة 2014 بتعديل بعض أحكام قانون الجامعات الصادر بالقانون رقم 49 لسنة 1972 -- قرار رئيس جمهورية مصر العربية بالقانون رقم 24 لسنة 2014 بتعديل بعض أحكام قانون الجامعات الصادر بالقانون رقم 49 لسنة 1972